2017
DOI: 10.2147/cmar.s139305
|View full text |Cite
|
Sign up to set email alerts
|

Impact of abiraterone on patient-related outcomes in metastatic castration-resistant prostate cancer: current perspectives

Abstract: Abiraterone acetate has established a major role in the treatment paradigm of metastatic castration-resistant prostate cancer ever since pivotal trials, COU-AA-301 and COU-AA-302, have shown benefit in both the second-line and first-line (post- and pre-chemotherapy) setting, respectively, with improvement in overall survival as well as secondary end points such as prostate-specific antigen (PSA) and radiographic response rates, time to PSA progression, and progression-free survival. There has been a lot of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“… 7 8 Although extending life expectancy is considered the gold standard for treatment, HRQoL is increasingly being considered an important endpoint. 25 AAP-treated and ENZ-treated patients showed more favourable PROs than controls in clinical trials 7 8 ; however, the effect of AAP compared with ENZ in terms of PROs, and cognition in particular, has not been extensively studied. Furthermore, data comparing the effects of these agents on PROS in the real-world setting are limited.…”
Section: Discussionmentioning
confidence: 99%
“… 7 8 Although extending life expectancy is considered the gold standard for treatment, HRQoL is increasingly being considered an important endpoint. 25 AAP-treated and ENZ-treated patients showed more favourable PROs than controls in clinical trials 7 8 ; however, the effect of AAP compared with ENZ in terms of PROs, and cognition in particular, has not been extensively studied. Furthermore, data comparing the effects of these agents on PROS in the real-world setting are limited.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing awareness that HRQoL is an important endpoint of value to both patients and healthcare providers. While the impact of treatments on many aspects of HRQoL in patients with localized disease is well established, there is less information on patients with advanced disease who are more likely to have poor performance status, are more frequently affected by pain due to bone metastases, and for whom the balance between longevity and quality of life is perhaps more important ( 125 , 126 ). A recent systematic review of patient values, preferences, and expectations found that, while cancer progression or survival, pain, and fatigue were key considerations regarding treatment decisions, alleviation of pain was valued at the expense of survival benefits among symptomatic patients ( 127 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following the demonstration of efficacy of abiraterone and enzalutamide in CRPC patients, that inform the use of these agents in current clinical practice, ongoing studies are moving forward to the use of these two drugs in an earlier phase of disease. Abiraterone was found to delay the FACT-P score deterioration when compared to placebo, in both post-chemotherapy and pre-chemotherapy settings (48). Abiraterone also proved to decrease the time to worst pain intensity palliation, defined as two consecutive follow-up visits (≥4 weeks apart) at which the worst pain intensity score was ≥30% lower than baseline, without an increase in analgesic use, in patients already treated with docetaxel (COU-AA-301).…”
Section: Impact Of New Generation Hormonal Therapies On Quality Of Lifementioning
confidence: 96%